Linking Local Community Initiatives, Aspirations and Conservation: Lessons from Dalma Sanctuary in Bihar - Srivastava, Sanjay (Indian Forester, 2000)
The management of Protected Areas is complex due to high pressure of people living in and around them. This paper deals with a case study of Dalma Wildlife Sanctuary in Bihar where local communities in and around the Sanctuary organized themselves in form of informal village Forest Protection Committees and controlled the grazing of cattle, illicit felling and annual tribal hunt and catalysed the natural regeneration without any financial support.